1994
DOI: 10.1111/j.1525-1594.1994.tb02228.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Molecular Clearance Rates During Continuous Hemofiltration and Hemodialysis with a Novel Volumetric Continuous Renal Replacement System

Abstract: We developed a continuous, volumetrically controlled veno-venous renal replacement system that can be operated in filtration or dialysis modes. We compared the clearances of substances with a range of molecular weights (MW) in each mode. Ten patients with acute renal failure underwent serial postdilutional hemofiltration and hemodialysis, for 30 min each, in sequence and in randomized order. All were receiving vancomycin for concurrent sepsis. The system incorporated a Filtral 10 AN69 artificial kidney; blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 7 publications
1
27
0
Order By: Relevance
“…Our experiments do not directly address clearance of uric acid, potassium, or phosphate. Uric acid and potassium are both low molecular weight molecules that are readily cleared by diffusion, although there is evidence that uric acid, which has a higher molecular weight than creatinine, is not cleared by dialysis as efficiently as creatinine (25) less efficient than convection (15). Isolated severe hyperkalemia in a neonate was treated effectively with continuous hemofiltration but, based on extrapolation of our study, may be more rapidly corrected with continuous hemodialysis (26).…”
Section: Discussionmentioning
confidence: 61%
“…Our experiments do not directly address clearance of uric acid, potassium, or phosphate. Uric acid and potassium are both low molecular weight molecules that are readily cleared by diffusion, although there is evidence that uric acid, which has a higher molecular weight than creatinine, is not cleared by dialysis as efficiently as creatinine (25) less efficient than convection (15). Isolated severe hyperkalemia in a neonate was treated effectively with continuous hemofiltration but, based on extrapolation of our study, may be more rapidly corrected with continuous hemodialysis (26).…”
Section: Discussionmentioning
confidence: 61%
“…AKI was defined by abnormal biochemistry (serum creatinine or urea) or a complication of oliguria (such as volume overload, hyperkalemia, acidosis or uremic symptoms) in 7 of 10 parallel-group trials [21,23-26,29,30] and 3 of 9 crossover trials [34,35,38]. The remaining nine trials enrolled patients with AKI requiring RRT without reporting specific AKI criteria [22,27,28,31-33,36,37,39]. Five trials explicitly excluded patients with chronic kidney disease, defined by pre-morbid creatinine or creatinine clearance [23,25,26,29] or recent dialysis [30],…”
Section: Resultsmentioning
confidence: 99%
“…Six of nine crossover trials [31,33,34,36-38] compared hemofiltration and hemodialysis at similar doses. Of these, only three trials reported post-filter addition of replacement fluid [33,37] or appropriately adjusted the rate of pre-filter replacement fluid to compare similar clearances [38]. Patients in one of these three trials [37] received three treatments (post-filter hemofiltration, pre-filter hemofiltration and hemodialysis) in random order.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with our knowledge of CH. Being a purely convective therapy, CH is efficient in clearing larger molecules [3,20,21]. Clearance of iohexol during CH as measured by SC was reliable through the range of Quf used most often in contemporary practice (Quf 1-3 l/h) as well as through the high-volume hemofiltration (Quf 6 l/h) occasionally used to manage sepsis [22].…”
Section: Discussionmentioning
confidence: 99%